2023
DOI: 10.3389/fnut.2023.1034481
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory processes involved in the alteration of liver function biomarkers in adult hospitalized patients treated with parenteral nutrition

Abstract: IntroductionLiver damage has been associated with the accumulation of phytosterols (PS) in patients treated with parenteral nutrition (PN). We aimed to study the association of inflammatory markers with liver function biomarker (LFB) alterations in patients treated with PN containing PS.Materials and methodsProspective observational study. Simple linear and stepwise multiple linear regression tests and interactions were performed.ResultsNineteen patients were included. In the multivariable model, determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Previous studies evaluating the effect of PN enriched with ω3 LE on the immune response of patients with gastric or colorectal tumors found significant differences between groups in reducing the inflammatory response, measured by parameters like IL-6, CRP, and TNF-α [ 18 , 21 ]. In our previous study [ 24 ], we also observed that for longer periods of PN, inflammation in the presence of plasmatic phytosterols (PS) exhibits a synergistic effect on impairing hepatic function, mainly altering GGT but also ALT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies evaluating the effect of PN enriched with ω3 LE on the immune response of patients with gastric or colorectal tumors found significant differences between groups in reducing the inflammatory response, measured by parameters like IL-6, CRP, and TNF-α [ 18 , 21 ]. In our previous study [ 24 ], we also observed that for longer periods of PN, inflammation in the presence of plasmatic phytosterols (PS) exhibits a synergistic effect on impairing hepatic function, mainly altering GGT but also ALT.…”
Section: Discussionmentioning
confidence: 99%